2008
DOI: 10.1016/j.aorn.2008.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Fasting Duration and Medication Instruction: Are We Improving?

Abstract: Research has shown that preoperative fasting practices commonly are much longer than national guidelines, and medication instructions are not always given to patients before surgery. After implementation of an evidence-based preoperative fasting policy and educational efforts for health care providers at one facility, a follow up project was conducted to determine whether these efforts had improved fasting practices. The project findings indicate that preoperative fasting in excess of safe minimum guidelines p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 35 publications
3
25
0
4
Order By: Relevance
“…Obviously we should intensify our education for health care professionals and caregivers. Behavioral changes concerning fasting times already pose a challenge in the developed world, 24 and easily overstretch our limited staff resources. It might seem easy to give the necessary information and training and to ask the question "when was the last time your child drank before the operation?…”
Section: Discussionmentioning
confidence: 99%
“…Obviously we should intensify our education for health care professionals and caregivers. Behavioral changes concerning fasting times already pose a challenge in the developed world, 24 and easily overstretch our limited staff resources. It might seem easy to give the necessary information and training and to ask the question "when was the last time your child drank before the operation?…”
Section: Discussionmentioning
confidence: 99%
“…9 Penelitian di Amerika Serikat menunjukkan durasi puasa makanan padat 6-37 jam dengan rata-rata 14,5 jam. 10 Hampir semua penelitian dan survei tentang puasa preoperatif mendapatkan hasil yang lebih lama daripada pedoman puasa preoperatif dari ASA 11 dan walaupun sudah diupayakan kampanye pedoman puasa preoperatif kepada dokter anestesi, dokter bedah, dan perawat di bangsal, hal ini tetap masih sulit diubah. 10 Puasa dari minuman rata-rata 8,06 jam dengan rentang durasi mulai dari 2 jam hingga 18 jam.…”
Section: 2unclassified
“…10 Hampir semua penelitian dan survei tentang puasa preoperatif mendapatkan hasil yang lebih lama daripada pedoman puasa preoperatif dari ASA 11 dan walaupun sudah diupayakan kampanye pedoman puasa preoperatif kepada dokter anestesi, dokter bedah, dan perawat di bangsal, hal ini tetap masih sulit diubah. 10 Puasa dari minuman rata-rata 8,06 jam dengan rentang durasi mulai dari 2 jam hingga 18 jam. Penelitian di Australia didapatkan puasa dari minuman rata-rata 9,4 jam, 9 sedangkan di Amerika Serikat durasi puasa dari minuman 3-20 jam dan rata-rata 11,9 jam.…”
Section: 2unclassified
“…Strict fasting rules implementation will lead to usual routine fasts after midnight (6). Moreover, experiences manifested that the fasting period is usually too long and its starting point is different from evening (after having dinner) to midnight, and it seems that this period is not related to surgery time and the patient's condition.…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of aspiration reported by Mendelson in 1946 was 0.15 percent that is five times more than the one (0.04percent) reported by Olsson et al,.Tirt et al, (0.01%) and Warner et al 's (0.04%) finding. Digestion period is subject to the kind of consumed food, the fasting time around 6 h is enough for making sure of gastric depletion, and it has been proved that such a long stretching of fast is unnecessary for liquids consumption before surgery (6,7). Liquids and water remain in stomach for only 12 minutes and surveys have revealed that the volume and PH of stomach or plasma osmolarity would not be affected by unlimited water intake until 2 h prior to surgery (8).…”
Section: Introductionmentioning
confidence: 99%